Practical aspects of the measurements of non‐photochemical chlorophyll fluorescence quenching in green microalgae Chlamydomonas reinhardtii using Open FluorCam. Issue 3 (25th July 2019) - Nowicka, Beatrycze
Abstract : Methods of chlorophyll fluorescence measurements are widely used in the research on photosynthesis and ecophysiology of plants and algae. Among them, a very popular technique is pulse‐amplitude‐modulation (PAM) flourometry, which is simple to carry out, fast and non‐invasive. However, this method is also prone to generate artifacts if the experiments were not planned and executed properly. Application of this technique to algae brings additional complications, which need to be taken into consideration. Some of them are connected with sample preparation and setting of the protocols used, while another origin from the differences in the photosynthetic apparatus and regulation of photosynthesis in various algal groups when compared to vascular plants. In the present paper, some important practical aspects concerning PAM fluorometry measurements in the green microalga Chlamydomonas reinhardtii have been described, including the equipment settings and sample preparation. The impact of growth conditions, such as light, temperature and medium type on the induction of non‐photochemical quenching of chlorophyll fluorescence have been also tackled, as well as the question of state transitions occurring in darkness.